1987
DOI: 10.1128/mcb.7.1.512
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new common provirus integration site in gross passage A murine leukemia virus-induced mouse thymoma DNA.

Abstract: The Gross passage A murine leukemia virus (MuLV) induced T-cell leukemia of clonal (or oligoclonal) origin in inoculated mice. To study the role of the integrated proviruses in these tumor cells, we cloned several newly integrated proviruses (with their flanking cellular sequences) from a single tumor in procaryotic vectors. With each of the five clones obtained, a probe was prepared from the cellular sequences flanking the provirus. With one such probe (SS8), we screened several Gross passage A MuLV-induced S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…Since the human genes for glutamine oxaloacetic transaminase (GOT) and for TdT map to region lOq25-q26 and 0q23-q24, respectively, and the homologous genes of the mouse map to mouse chromosome 19, it appears that the region involved in the t(10;14) chromosome translocation in man is homologous to a region of mouse chromosome 19. It is of considerable interest that Villemur et al (16) have found that murine leukemia virus integrates into a specific region of mouse chromosome 19 in -25% of virus-induced T-cell leukemias that they have analyzed. Thus it seems possible that the putative TCL3 gene, which is activated by the translocation of the TCR gene in man, might be activated by retroviral insertion in the mouse.…”
Section: Resultsmentioning
confidence: 99%
“…Since the human genes for glutamine oxaloacetic transaminase (GOT) and for TdT map to region lOq25-q26 and 0q23-q24, respectively, and the homologous genes of the mouse map to mouse chromosome 19, it appears that the region involved in the t(10;14) chromosome translocation in man is homologous to a region of mouse chromosome 19. It is of considerable interest that Villemur et al (16) have found that murine leukemia virus integrates into a specific region of mouse chromosome 19 in -25% of virus-induced T-cell leukemias that they have analyzed. Thus it seems possible that the putative TCL3 gene, which is activated by the translocation of the TCR gene in man, might be activated by retroviral insertion in the mouse.…”
Section: Resultsmentioning
confidence: 99%
“…Leukemias induced by other retroviruses containing proviral insertions near c-myc appear to be clonal or oligoclonal (56,58). Why are tumors induced by TBLV polyclonal?…”
Section: Discussionmentioning
confidence: 99%
“…The TCR[~ RBL5 and Moloney U3 LTR fragment have been described previously (Paquette et al 1992). The DNA probes used to search for DNA rearrangements were: V/r~l (pro.6) (Hanna et al 1993), Ginl (SS8) (Villemur et al 1987), Misl (pM1FR2) (Villeneuve et al 1986), BmiI (van Lohuizen et al 1991, Pall (pl la2) (van Lohuizen et al 1991), Ahil (Poirier et al 1988), and Piml (Selten et al 1984). All probes were labeled with [~2PldCTP and [32p]dATP by the random primer method, as described previously {Hanna et al 1993).…”
Section: Probesmentioning
confidence: 99%
“…A genomic library of BamHI-digested DNA from tumor T3481 was constructed by ligation into the arms of a phage EMBL-3 vector and screened by hybridization with 32p-labeled Moloney U3 LTR-specific probe, essentially as described previously (Villemur et al 1987;Poirier et al 1988). The Notch1 genomic sequences used for mapping exons E and F were isolated from a normal BALB/c genomic a library.…”
Section: Molecular Cloning Proceduresmentioning
confidence: 99%
See 1 more Smart Citation